Analysis of Income and Costs Against Profit Using the Common Size Technique at Grand Cempaka Resort & Convention in Bogor Regency 2018-2021 - Mohamad Fikriansyah; Muhammad Nur Afif; Ayi Jamaludin Aziz; Yuppy Triwidatin (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
Financial reports are one of the main keys for a company to find out how well the company carries out its business activities, of course the main purpose of financial reports is to track the income realized by the company, therefore financial reports are an important thing that must be owned and must be monitored in order to improve the company's financial performance so that even better. The aim of this research is to determine the development of items on the balance sheet and profit and loss as well as financial performance at the Grand Cempaka Resort & Convention for the 2018-2021 period. To find out the results of this problem, researchers used a quantitative descriptive research system, namely the common size analysis technique. The results of this research conclude that the company is experiencing instability in its financial performance which we can see from the results of the common size analysis calculations on balance sheet and profit and loss items during the 2018-2021 period.